2018
DOI: 10.1186/s40729-018-0119-5
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of dental implants with validation: to what extent can we expect the model to predict biological phenomena? A literature review and proposal for classification of a validation process

Abstract: A literature review of finite element analysis (FEA) studies of dental implants with their model validation process was performed to establish the criteria for evaluating validation methods with respect to their similarity to biological behavior. An electronic literature search of PubMed was conducted up to January 2017 using the Medical Subject Headings “dental implants” and “finite element analysis.” After accessing the full texts, the context of each article was searched using the words “valid” and “validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 69 publications
3
51
0
3
Order By: Relevance
“…However, when multiple design changes are made, the results derived by previous research cannot be used. To quickly analyze and predict the differences resulting from design changes in dental implant systems, the FEA is a mathematical model analysis that has been widely used in implant dentistry [12]. Therefore, this study was carried out using FEA to compare the mechanical behavior relative to design changes, including changes to implant body shape, implant collar shape, thread design and pitch, of a new dental implant design with a standard implant design with the same diameter and length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when multiple design changes are made, the results derived by previous research cannot be used. To quickly analyze and predict the differences resulting from design changes in dental implant systems, the FEA is a mathematical model analysis that has been widely used in implant dentistry [12]. Therefore, this study was carried out using FEA to compare the mechanical behavior relative to design changes, including changes to implant body shape, implant collar shape, thread design and pitch, of a new dental implant design with a standard implant design with the same diameter and length.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of data about the implant macro-design (body and neck) and threads design that can optimize the maintenance of peri-implant bone. In order to predict stress and strain within structures in a real situation, which cannot be solved by a traditional linear static model, nonlinear finite element analysis (FEA) is a mathematical model analysis that allows for evaluating, in a qualitatively detailed way, the mechanical behavior of dental implants, especially the stress distribution generated at the implant/bone interface [12]. In this study, a new type of dental implant, designed with the intention of creating stress initially at cancellous bone and to reduce the stress peaks in the surrounding upper cortical bone, was evaluated by FEA.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review performed by Chang et al . [ 30 ] in 2018 found that among 450 publications over the last 10 years about dental implants using FEA, only 47 articles used some kind of validation (clinical or laboratory experiments, findings in the literature, or another kind of validation), and the strain gauge method of laboratory testing was used in 15 of those 47 articles. That review recognized that simplifying the biomechanical behavior of tissues and ignoring the characteristics of each individual for computer analysis may neglect some aspects, resulting in inaccuracies in the predicted behavior of structures in the studied circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical simulation analysis by finite elements and its validation through extensometry, photoelasticity, photogrammetry, fractal analysis and, most recently, DIC (digital image correlation) [6][7][8][9][10] are some of the most commonly used in vitro methods to evaluate results according to the load conditions and other characteristics of a given experiment. Anyway, since the simulation demands experimental verification to determine the long-term resistance of the components under real loads, it is of vital importance to conduct fatigue tests under the most realistic loads and effective chewing conditions possible.…”
Section: Introductionmentioning
confidence: 99%